Turner and the Mystery of the Sea - Malcolm Andrews (Caliban: French Journal of English Studies, 2014)
The great English landscape painter J.M.W.Turner was an anomalous presence in Victorian England. He and his work were admired and reviled; he was a devoted supporter of the traditional institution, the Royal Academy – a bulwark of the conservative establishment – and at the same time his radical artistry and extravagant colouring offended traditionalists; he was a respected Professor of the Academy and in his private life, living with his mistress, he could be a scruffy, gruff bohemian. He was both Prospero and Caliban, the powerful magician with paint, and the rebellious, surly Caliban. This paper traces Turner’s artistic relationship with the sea, his extraordinary understanding of its moodiness, its violence and its serenity, and it associates his art with the sea poetry of his contemporaries, Swinburne and G.M.Hopkins. Like Caliban’s profound instinctive responsiveness to natural music, Turner’s feel for the mercurial beauty and savagery of the sea found exquisite and often disturbing poetic expression.